Green HR practices and environmental performance: The mediating mechanism of employee outcomes and moderating role of environmental values - Adeel, Muhammad; Mahmood, Shahid; Khan, Kanwal Iqbal; Saleem, Saima (Frontiers in Environmental Science, 2022)
Scholars focused on behavioral changes in employees rather than depending solely on technology enhancements due to organizations’ poor and inefficient environmental performance. The purpose of this research is to observe the influence of green HR practices (GHRP) on work engagement and job satisfaction in the environment and its effect on the environmental performance of universities. Furthermore, the mediating effect of work engagement and job satisfaction and moderating impact of environmental values are explored. The data were collected from 337 officials and faculty members of universities of Pakistan through structured questionnaires. The SPSS process macros results indicate that GHRP significantly impacts environmental performance, job satisfaction, and work engagement. The mediation results reveal that work engagement and job satisfaction acted as a means by which GHRP of universities can positively affect environmental performance. The moderation results reveal that environmental values strengthen the relation of GHRP with environmental performance. The study highlights the significance and importance of GHRP for environmental performance and extends the literature by shedding light on the role of employee outcomes and environmental values.